Review on the Utility of Trabecular Bone Score, a Surrogate of Bone Micro-architecture, in the Chronic Kidney Disease Spectrum and in Kidney Transplant Recipients - Shevroja, Enisa; Lamy, Olivier; Hans, Didier (Frontiers in Endocrinology, 2018)
Chronic kidney disease (CKD) is defined as abnormalities of kidney structure or function, present for >3 months, with implications for, among others, bone health. Advanced stages of CKD have an increased risk of fragility fractures. Trabecular bone score (TBS) is a relatively new gray-level textural parameter, which provides information on bone micro-architecture and has been shown to be a good predictor of fragility fractures independently of bone density and clinical risk factors. We aimed to review the scientific literature on TBS and its utility along the CKD spectrum and in kidney transplant recipients. In total, eight articles had investigated this topic: one article in patients with reduced kidney function, two in patients on hemodialysis, and five in kidney transplant recipients. In general, all the studies had shown an association between lower values of TBS and reduced kidney function; or lower TBS values among the hemodialysis or kidney transplant patients compared to healthy controls. Moreover, TBS was shown to be a good and independent predictor of fragility fractures in patients with CKD or who underwent kidney transplantation. TBS postulates itself as a valuable marker to be used in clinical practice as an assessor of bone micro-architecture and fracture risk predictor in these specific populations. However, evidence is to some extent limited and larger follow-up case-control studies would help to further investigate the TBS utility in the management of bone health damage and increased fracture risk in patients with CKD or kidney transplant.